Novel 2-oxoimidazolidine-4-carboxylic acid derivatives as Hepatitis C virus NS3-4A serine protease inhibitors: synthesis, activity, and X-ray crystal structure of an enzyme inhibitor complex - Arasappan, Ashok; Njoroge, F. George; Parekh, Tejal N.; Yang, Xiaozheng; Pichardo, John; Butkiewicz, Nancy; Prongay, Andrew; Yao, Nanhua; Girijavallabhan, Viyyoor (Bioorganic & medicinal chemistry letters, 2004)
Synthesis and HCV NS3 serine protease inhibitory activity of some novel 2-oxoimidazolidine-4-carboxylic acid derivatives are reported. X-ray structure of an inhibitor, 15c bound to the protease is presented. Synthesis and HCV NS3 serine protease inhibitory activity of some novel 2-oxoimidazolidine-4-carboxylic acid derivatives are reported. Inhibitors derived from this new P2 core exhibited activity in the low μM range. X-ray structure of an inhibitor, 15c bound to the protease is presented.